Extinction and beyond: an expanded framework for exposure and response prevention for obsessive-compulsive disorder - Berg, Hannah; Webler, Ryan D.; Klein, Samuel; Kushner, Matt G. (Frontiers in Psychology, 2024)
Exposure therapy is a first-line, empirically validated treatment for anxiety, obsessive-compulsive, and trauma-related disorders. Extinction learning is the predominant theoretical framework for exposure therapy, whereby repeated disconfirmation of a feared outcome yields fear reduction over time. Although this framework has strong empirical support and substantial translational utility, extinction learning is unlikely to be the sole process underlying the therapeutic effects of exposure therapy. In our clinic, we commonly treat obsessive-compulsive disorder (OCD) patients successfully with exposure therapy even when some or all of their feared outcomes are not amenable to disconfirmation and, by extension, to extinction learning.Herein, we present a generic clinical vignette illustrating a commonly encountered feared outcome in OCD that cannot be disconfirmed through exposure (damnation resulting from blasphemous thoughts). We describe two specific non-extinction based strategies we commonly employ in such cases, and we associate these strategies with known change mechanisms that might account for their effectiveness: (1) non-associative habituation to aversive stimuli, and (2) fear-memory elicitation and subsequent reconsolidation. We discuss the limitations inherent in the reverse-translational approach taken and its opportunities for expanding the framework of exposure therapy.